Drug design: 4-thiazolidinones applications. Part 2. Pharmacological profiles (Journal of Medical Science, 2020)
Following of the chemical diversity of 4-thiazolidinones the in-house library of new heterocycles have been designed and synthesized (more 7000 compounds). Anticancer, antitrypanosomal, antituberculosis and antiviral activity screening led to SAR database formation; lead-compounds identification; design of focused sub-libraries; formation and validation of hypotheses for structure optimization: i) complications of C5 fragment and/or functionalization of N3 position; ii) creation of the hybrid molecules; iii) fixation of 5-ene-4-thiazolidinones in fused heterocycles via annulation (thiopyrano[2,3-d]thiazoles were found as a cyclic isosteric mimetics of 5-ene-4-thiazolidinones); iv) the leukemia panel was detected to be the most sensitive among all cancer cell lines. Following the in silico and pharmacological data for the investigation of molecular mechanism of anticancer effect the argument in favor of the apoptotic related and mild prooxidant actions for active compounds have been found.